2016
DOI: 10.1016/j.ntt.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary lacks sexual dimorphism and displays reduced signal intensity on T1-weighted MRI in adolescents with histories of heavy prenatal alcohol exposure

Abstract: Prenatal alcohol exposure can interfere with endocrine function and have sex-specific effects on behavior. Disrupted development of the pituitary gland, which has been observed in rodent studies, may account for some of these effects. To determine if gestational exposure to alcohol produces measureable changes in the pituitary in human adolescents, we manually traced the pituitary in T1-weighted structural magnetic resonance images (MRI) from adolescents with (15 males, 11 females) and without (16 males, 11 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
2
2
0
Order By: Relevance
“…PAE effects on the adult pituitary were sex dependent; in males, PAE increased pituitary size, while in females, PAE decreased pituitary size, effectively attenuating the inherent sex difference in the mouse pituitary. Similar effects of PAE on pituitary volumes have been observed in adolescent humans (Moore et al, 2016), and the current results suggest that early alcohol exposure may have been sufficient for those structural changes. In the small sample size available from the current dataset, pituitary volume changes were correlated with distinct behaviors in males and females, distance travelled in the center of the open field and time with the familiar social stimulus during the novelty phase, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…PAE effects on the adult pituitary were sex dependent; in males, PAE increased pituitary size, while in females, PAE decreased pituitary size, effectively attenuating the inherent sex difference in the mouse pituitary. Similar effects of PAE on pituitary volumes have been observed in adolescent humans (Moore et al, 2016), and the current results suggest that early alcohol exposure may have been sufficient for those structural changes. In the small sample size available from the current dataset, pituitary volume changes were correlated with distinct behaviors in males and females, distance travelled in the center of the open field and time with the familiar social stimulus during the novelty phase, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Only one longitudinal study to date has modeled the interactions of group, sex, and age in their analysis (Lebel et al, 2012 ) and noted areas in the left hemisphere where sexually dimorphic cortical trajectories may be attenuated for those with PAE. This finding replicates previous studies that have noted attenuated sex-differences in the brain among youth with PAE (Moore et al, 2016 ; Treit et al, 2017 ; Inkelis et al, 2020 ). Moreover, one cross-sectional study showed altered white-matter developmental trajectories in males but not in females (Uban et al, 2017 ).…”
Section: Future Directionssupporting
confidence: 91%
“…Arginine vasopressin (AVP), a hormone produced and stored in the pituitary gland, has been linked to insulin signaling with lower levels producing insulin hypersensitivity (Fujiwara et al, 2007). Reductions in the volume of the pituitary gland and lower AVP levels have been found in both preclinical models of PAE (Bird et al, 2006; Knee et al, 2004) and a clinical sample of children with FASDs (Moore et al, 2016). Neuroimaging studies of the HPA access, including the pituitary gland, may be needed to help with understanding CNS involvement in the abnormal insulin levels found in this sample.…”
Section: Discussionmentioning
confidence: 99%